2014
DOI: 10.1093/brain/awu231
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin improves behavioural and neural deficits in inferring others’ social emotions in autism

Abstract: Recent studies have suggested oxytocin's therapeutic effects on deficits in social communication and interaction in autism spectrum disorder through improvement of emotion recognition with direct emotional cues, such as facial expression and voice prosody. Although difficulty in understanding of others' social emotions and beliefs under conditions without direct emotional cues also plays an important role in autism spectrum disorder, no study has examined the potential effect of oxytocin on this difficulty. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
119
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(123 citation statements)
references
References 75 publications
2
119
0
2
Order By: Relevance
“…Although there is no clinical use of minocycline in ASD, recent studies have revealed improvement of ASD symptoms by intranasal administration of oxytocin and demonstrated the association of polymorphisms in the oxytocin receptor (OXTR) gene in ASD (Andari et al, 2010;Guastella et al, 2010;Aoki et al;2014;LoParo and Waldman, 2015). Furthermore, abnormal activation of microglia and a reduction of PSD-95 expression in the Oxtr-deficient brain (Miyazaki et al, 2016) have been found.…”
Section: Pharmacological Approach To Neuroinflammation In Asd and Schmentioning
confidence: 99%
“…Although there is no clinical use of minocycline in ASD, recent studies have revealed improvement of ASD symptoms by intranasal administration of oxytocin and demonstrated the association of polymorphisms in the oxytocin receptor (OXTR) gene in ASD (Andari et al, 2010;Guastella et al, 2010;Aoki et al;2014;LoParo and Waldman, 2015). Furthermore, abnormal activation of microglia and a reduction of PSD-95 expression in the Oxtr-deficient brain (Miyazaki et al, 2016) have been found.…”
Section: Pharmacological Approach To Neuroinflammation In Asd and Schmentioning
confidence: 99%
“…Indeed, experimenter-administered OT augments behavioral performance in emotion recognition, relieves some social deficits observed in individuals with ASD; and increases insular activity and connectivity to frontal cortex [43][44][45] . Furthermore, mutations in the OTR gene predict ASD symptoms 46 , insular activation 47 and social cognition 48,49 .…”
mentioning
confidence: 99%
“…In an elegant paper recently published in Brain, oxytocin was shown to enhance both the score of correct inferences and the low autistic brain activity in the right anterior insula when inferring the emotions and beliefs of others (Aoki et al, 2014). Using a revisited version of the Sally-Anne Task, Aoki and colleagues suggest that reduced activity of the right anterior insula is a potential neural marker of autistic deficit in social inferences.…”
mentioning
confidence: 99%
“…The following firstlevel individual t-contrast images were obtained for the haemodynamic response function estimates: 'being imitated versus observation' and 'observation versus being imitated'. We focused the second-level analysis on the insula and the default mode network with an a priori region of interest approach (Guionnet et al, 2012;Aoki et al, 2014). A paired t-test analysis was performed to assess the difference in activation of the insula and default mode network between both MRI scans.…”
mentioning
confidence: 99%